(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
The ideology of Indonesian preachers in expressing their opinions and views on a matter is a significant factor in the digital age in influencing their followers. On that basis, this study aims to determine the ideology of Indonesian preachers in discussing political discourse on Youtube social media. This study uses a qualitative research design and uses data from videos derived from 25 YouTube videos in several categories of interpretive figures such as Adi Hidayat, Buya Yahya, Das’ad Latif, Khalid Basalamah, Syafiq Riza Basalama. The data collection techniques include observation and documentation and data analysis techniques through discourse analysis to uncover patterns and themes in the text delivered by the preachers. The results showed that: (1) preachers who discuss ideologies related to politics on social media have inclusive and exclusive perspectives; (2) political discourse obtained from social media is expected that leaders are expected to have qualified abilities from the cognitive intelligence element in leading a country and have a good attitude to oversee the people in general such as a fair attitude, being able to understand the conditions and needs of the country and good physical abilities to manage the wheels of government; (3) the understanding of followers of interpretative figures generally supports the ideology carried out but there are also those who provide criticism and different views; the factors that cause ideological contestation consist of figures who have charisma and delivery methods that are diverse and not monotonous.